Business Plan - Escape Game - Mazheyeu, Dzmitry; Houska, Daniel; Levý, Jan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The purpose of this thesis is to create a convincing Scary Escape Game business plan to present to future investors. The main topics that will be analyzed are the most important aspects of creating a business plan and were considered to one degree or another during the educational process. In order to formalize this project according to academic patterns, a wide list of literature will be reviewed and an academic methodology will be applied, which should compensate for the lack of experience of the author of the idea and take concepts that have already been proposed by the authors of the texts before in order to avoid critical errors and create a comprehensive plan. Scary Escape Games are a type of entertainment in which a small group of people (2-6 people) are placed in an immersive narrative. The result will be a forecast of the profitability of this business, a timeline, an assessment of the necessary resources, marketing and organizational decisions.
Vedoucí práce: Daniel Houska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses